2017
DOI: 10.1111/trf.14368
|View full text |Cite
|
Sign up to set email alerts
|

An international investigation into AB plasma administration in hospitals: how many AB plasma units were infused? The HABSWIN study

Abstract: BACKGROUND Typical practice is to transfuse group‐specific plasma units; however, there are situations where group AB plasma (universal donor) is issued to group A, B, or O recipients. If demand for group AB plasma exceeds collections, there is potential for shortage. This project explored the patterns of group AB plasma utilization at hospitals around the world. STUDY DESIGN AND METHODS The study had two phases: a survey that inquired about hospital group AB plasma inventory, policies, and transfusion practic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…When group AB plasma is thawed, perhaps in anticipation of use in an MTP, but not used, it can then be transfused to any other patient with a coagulopathy to avoid wastage. The results from a recent international retrospective investigation into group AB plasma transfusion practice in 15 hospitals indicated that group AB plasma was frequently transfused to non‐AB recipients, with only 27% of the group AB plasma units transfused to group AB recipients . Thus, supplying enough AB plasma to facilitate use in MTPs needs to be balanced against oversupplying this scarce resource such that it ends up being transfused to non–group AB patients to avoid wastage.…”
Section: Discussionmentioning
confidence: 99%
“…When group AB plasma is thawed, perhaps in anticipation of use in an MTP, but not used, it can then be transfused to any other patient with a coagulopathy to avoid wastage. The results from a recent international retrospective investigation into group AB plasma transfusion practice in 15 hospitals indicated that group AB plasma was frequently transfused to non‐AB recipients, with only 27% of the group AB plasma units transfused to group AB recipients . Thus, supplying enough AB plasma to facilitate use in MTPs needs to be balanced against oversupplying this scarce resource such that it ends up being transfused to non–group AB patients to avoid wastage.…”
Section: Discussionmentioning
confidence: 99%
“…60 The vast majority of AB plasma units are transfused to non-AB recipients. 61 Given the pressure on AB plasma stocks, it has not been possible to provide male-only AB plasma for all recipients, with resultant cases of transfusion-related acute lung injury from female AB plasma. 62 Hence, the draw of the group and screen sample, rapid transport of the sample to the laboratory and testing of the sample should be prioritized.…”
Section: Open Researchmentioning
confidence: 99%
“…However, as the prevalence for blood group AB in Germany is only about 6%, the access to AB plasma is limited despite targeted recruitment of AB plasma donors [ 5 ]. The need for AB plasma is consistently high as AB plasma is used as universal plasma and only 27% of AB plasma units transfused in 2014 in hospitals around the world were transfused to group AB recipients [ 6 ]. Three clinical situations are attractive for blood group independent transfusion of plasma.…”
Section: Introductionmentioning
confidence: 99%